Five have a mystery to solve - Blyton, Enid (Hodder Children's London, 2011)
ADVENTURE STORIES. New and contemporary cover treatment with carefully edited, timeless, text brings The Famous Five right into the 21st Century, and to a whole new generation of readers! Ages 9+